BRAND POSITIONING PADA HYPERMARKET DI KOTA PALEMBANG - Eko Fitrianto; Nazaruddin Ahmad; Islahuddin Daud (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
Heterogenity consumer induces companies do segmented marketing. Perception on brand also needs appropriate mapping to know the market position. This research aims to cluster the consumer according to their important attributes and creates perceptual mapping brand. The gained through the collection of primary data, with the total of 200 participants of hypermarket visitor in Palembang. The result show 3 clusters that are created with unique and varietetd at characteristics. Futhermore, the perceptual mapping shows that each hypermarket has their unique position compared to others. It could concluded that, when cluster of consumer and perceptual mapping are known, producers can serve consumer better